Food irradiation and development of an alternative method for the detection of 2-Alkylcylcyclobutanone - Amit, Kumar (Kansas State University, 2008)
Food irradiation is one of the most important food processing methods utilized to reduce microbial load and extend shelf life. In 1995 the World Health Organization (WHO) declared irradiated foods to be safe from a nutritional and toxicological point of view. Various methods have been applied to detect irradiated foods. Detection of 2-alkylcyclobutanones has been found to be a useful method in identifying irradiated foods. The solvent extraction method utilizes a Soxhlet apparatus for lipid extraction followed by clean up with Florisil. However, this method is very time consuming. The other methods available to detect 2-alkylcyclobutanone include supercritical fluid extraction (SFE), and accelerated solvent extraction method using a Dionex ASE 200 instrument. The SFE is a fast method to detected 2-alkylcyclobutanone. All the above mentioned methods involve costly equipment. The aim of this study was to eliminate the requirement of costly extraction equipment for lipid extraction before clean up or direct isolation of 2-alkylcyclobutanone as in case of SFE instrument using Florisil cartridges. In this study, the manual solvent extraction method was applied to isolate alkylcylcobutanone followed by clean up with 2 g silica cartridge. The clean up extract was injected to gas chromatography-flame ionization detector (GC-FID) for detection of 2-dodecylcyclobutanone (2-DCB). Gas chromatography-mass spectrometry (GC-MS) was used to confirm that the compound detected was 2-dodecylcyclobutanone. The ions m/z 98 and 112 were selected for 2-DCB for monitoring in selected ion monitoring (SIM) mode of GC-MS. The results showed that this method was able to detect 2-DCB from irradiated ground beef. The manual method does not require costly equipment such as supercritical fluid extractor, Dionex, or Soxlet apparatus for extraction process.
Keywords: Food Irradiation; 2-dodecylcyclobutanone; acetonitrile; silica cartridge; Agriculture, Food Science and Technology (0359)